Kualitas Pelayanan Kualitas Produk Terhadap Minat Beli Ulang Dengan Kepuasan Sebagai Variabel Intervening Pada Konsumen Matahari Departmen Store Sukabumi - Wiwin Darwati; Arif Adnan; Saeful Rachman (LPPM Sekolah Tinggi Ilmu Ekonomi PGRI Sukabumi, 2021)
This research is about consumer repurchase intention with the aim of analyzing satisfaction in mediating the effect of service quality and product quality on consumer repurchase intention. The data analysis method uses multiple regression and the Sobel test to test the effect. The population is Matahari Department Store Sukabumi consumers in the June 2020 Observation Period of 8500 consumers. By taking the sample using the Taro Yamane formula with an error rate of 10%. So that the number of samples is 100 respondents. The results show that service quality has an effect on repurchase intention, product quality has an effect on repurchase intention, satisfaction has an effect on repurchase intention, service quality has an effect on satisfaction, product quality has an effect on satisfaction, service quality and product quality are each able to mediate the influence of interest. repurchase through customer satisfaction at Matahari Department Store Sukabumi.